2007
DOI: 10.1002/cne.21489
|View full text |Cite
|
Sign up to set email alerts
|

Novel distribution of junctional adhesion molecule‐C in the neural retina and retinal pigment epithelium

Abstract: Junction adhesion molecules-A, -B, and -C (Jams) are cell surface glycoproteins that have been shown to play an important role in the assembly and maintenance of tight junctions and in the establishment of epithelial cell polarity. Recent studies reported that Jam-C mRNA was increased threefold in the all-cone retina of the Nrl(-/-) mouse, suggesting that Jam-C is required for maturation and polarization of cone photoreceptors cells. We examined the expression of Jams in the mouse retina by using confocal immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 60 publications
3
42
0
1
Order By: Relevance
“…The viral myocarditis pathway (hsa05416) contains CAV1 (Caveolin 1) previously shown to be associated with POAG (Thorleifsson et al 2010; Wiggs et al 2011). In the cell adhesion pathway, JAM2 is a component of the neural retina and retinal pigment epithelium (Daniele et al 2007) and PVRL3 has previously been shown to contribute to ocular developmental defects (Lachke et al 2012). …”
Section: Resultsmentioning
confidence: 99%
“…The viral myocarditis pathway (hsa05416) contains CAV1 (Caveolin 1) previously shown to be associated with POAG (Thorleifsson et al 2010; Wiggs et al 2011). In the cell adhesion pathway, JAM2 is a component of the neural retina and retinal pigment epithelium (Daniele et al 2007) and PVRL3 has previously been shown to contribute to ocular developmental defects (Lachke et al 2012). …”
Section: Resultsmentioning
confidence: 99%
“…A number of PM proteins that are sorted basolaterally in most epithelia have an apical or non-polar distribution in RPE cells. These include the Transferrin Receptor (TfR) (Perez Bay et al, 2013), the Coxsackie-Adenovirus Receptor (CAR) (Diaz et al, 2009), JAM C (Daniele et al, 2007) and the Neural Cell Adhesion Molecule (NCAM)(Gundersen et al, 1993). The apical localization of CAR and TfR results from the transcytosis of these receptors to the apical PM from common recycling endosomes (CRE) (Diaz et al, 2009; Perez Bay et al, 2013).…”
Section: Structural and Functional Polarity Of Rpe Cellsmentioning
confidence: 99%
“…Frozen sections of paraformaldehyde-fixed mouse eyes were prepared for immunohistochemical analysis and confocal imaging as previously described (11 Ϫ/Ϫ mice, and RPE-choroid and retinal lysates were prepared for immunoblot analysis as previously described (11,34).…”
Section: Animalsmentioning
confidence: 99%